Driver-Car Interaction and Safety Conference 2023 - Editorial, Foreword (Acta Polytechnica CTU Proceedings)
DCIS 2023 built on previous successful Driver-Car Interaction and Safety Conferences and represented a continuity in a good tradition of sharing actualities of research and industry in the area of driver safety and issues of human-machine interaction. The trending topic of this year's conference was connected to autonomous and sustainable transport, smart cities, personal mobility and logistics. Both researchers from academia (graduate -Master and doctoral students, faculty) and experts from industry joined this event. The conference was opened to participants coming from areas of basic and/or applied research, forensic experts' departments, car industries, design and ergonomics, medical research etc.